CoSeO3 / NF electrode material for SOR and HER reactions and preparation method thereof

By synthesizing CoSeO3/NF electrode materials in situ on porous nickel foam, the problem of poor electrocatalytic activity in the prior art is solved, and efficient sulfur oxidation and hydrogen evolution reactions are achieved, which are suitable for sulfur recovery and hydrogen regeneration.

CN119710761AActive Publication Date: 2025-03-28CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411859486.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

In the prior art, electrode materials with SOR and HER electrocatalytic activity have a high overpotential and poor catalytic activity.

Method used

CoSeO3/NF electrode material is used to remove oxides and impurities on the surface of the porous foam nickel, and add Co and Se sources to conduct hydrothermal reactions to form a CoSeO3/NF electrode material with a sea urchin-like structure.

Benefits of technology

It realizes efficient sulfur oxidation reaction and hydrogen evolution reaction under mild conditions, reduces energy barriers, improves electrocatalytic activity and stability, and is suitable for sulfur recovery and hydrogen regeneration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710761A_ABST
    Figure CN119710761A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electro-catalysis, in particular to a CoSeO3 / NF electrode material for SOR and HER reactions and a preparation method of the CoSeO3 / NF electrode material. A bifunctional catalyst with SOR and HER electrocatalytic activity at the same time is high in overpotential and poor in catalytic activity. Aiming at the technical problems, the invention provides the CoSeO3 / NF electrode material for SOR and HER reactions, a catalyst with a sea urchin-shaped structure formed by a CoSeO3 micron sheet layer is synthesized in situ on a three-dimensional porous foamed nickel substrate through a simple one-step hydrothermal method, and due to the special structure of the catalyst, the number of active sites on the surface of the catalyst is greatly increased, so that the surface activity of the catalyst is improved, and the service life of the catalyst is prolonged. Compared with the prior art, the catalyst provided by the invention provides a richer electron transmission path, so that the mass transfer efficiency is effectively improved, and the catalyst shows relatively high catalytic activity on SOR and HER reactions, and has a relatively good application prospect in the aspects of sulfur recovery and efficient hydrogen regeneration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalysis, and in particular to a CoSeO3 / NF electrode material for SOR and HER reactions and a preparation method thereof. Background Art

[0002] Sulfur is a valuable commodity that is widely used in various industries, including chemistry, agrochemicals, rubber, cosmetics, fertilizers and pharmaceuticals. At the same time, sulfur is also the main precursor of sulfuric acid, which is considered an important chemical in the world economy. However, with the increasing number of pharmaceutical and chemical companies and the rapid development of coking, petroleum, and leather industries, sulfides are widely present in industrial wastewater and waste gas. These sulfur-containing wastes are extremely polluting to the atmosphere and water resources. They are not only smelly, toxic and corrosive, but also cause serious pollution to people's lives and industrial production. In view of this, it is particularly urgent to study and develop the recycling technology of sulfur-containing wastes.

[0003] The current recycling processes for sulfur-containing waste include the following types:

[0004] (1) Claus process is to recover acidic gases (H2S and CO2) from acidic raw materials and process them in a sulfur recovery unit (SRU) to obtain sulfur. However, Salisu Ibrahim et al. (DOI: 10.1016 / j.ces.2017.06.050) found that frequent changes in the composition of acidic gases often lead to lean acidic gases (i.e., CO2 has a higher content). The flame instability caused by lean acidic gases will destroy the feed gas in the Claus furnace, resulting in the need to continuously optimize the amount of fuel gas injected into the Claus furnace, which complicates the process flow and is not conducive to industrial development.

[0005] (2) The SulFerox process simplifies the Claus unit by directly removing hydrogen sulfide from the gas stream and converting it into sulfur, which greatly saves operating costs. However, Yunbo Wang et al. (DOI: 10.3969 / j.issn.1005-8168.2022.04.001) pointed out that the sulfur recovery rate of the SulFerox process is low and cannot meet the national standards for SO2 emissions.

[0006] (3) The LO-CAT process is a liquid phase catalytic oxidation sulfur recovery technology that uses water as a medium and a renewable iron ion complex catalyst. The process is simple, the degree of desulfurization is high, and it meets environmental protection requirements. However, Xu Fan et al. (Fan Xu, Wang Xiangping, Li Zhiqiang, et al. Research on iron ion loss in LO-CAT sulfur recovery process [J]. Nitrogen Fertilizer, 2023, 46(05): 289-295.) reported that the LO-CAT agent used in the LO-CAT process had abnormally low iron ion content many times, requiring concentrated replenishment of a large amount of the agent. It cannot be used stably for a long time in the actual production process, causing huge economic losses.

[0007] It can be seen that various industrial sulfur recovery methods have their own advantages and disadvantages. In order to further improve the sulfide removal technology, we urgently need to develop a new treatment solution with simple process flow, mild reaction conditions, low cost, high efficiency and environmental friendliness.

[0008] In recent years, the electrochemical oxidation method has gradually attracted the attention of scholars. The electrochemical oxidation method can simultaneously carry out electrochemical sulfur oxidation reaction (SOR) and hydrogen evolution reaction (HER) on sulfur-containing wastewater, which can not only convert the S element in the sulfur-containing wastewater into sulfur, but also obtain clean energy hydrogen. However, the current bifunctional catalysts that have both SOR and HER electrocatalytic activity are not very active and have a high overpotential, which needs further improvement. Summary of the invention

[0009] The problem in the prior art is that the electrode material having both SOR and HER electrocatalytic activity has a high overpotential and poor catalytic activity. In view of the above technical problems, the present invention provides a CoSeO3 / NF electrode material for SOR and HER reactions, and the preparation method thereof comprises the following steps:

[0010] (1) removing oxides and impurities on the surface of porous nickel foam to obtain a nickel foam carrier;

[0011] (2) adding a Co source and a Se source into deionized water, stirring and dispersing them uniformly to obtain a dispersion, adding an ammonium salt into the dispersion to adjust the pH of the solution to 1-3, and obtaining a catalyst solution;

[0012] (3) The nickel foam carrier obtained in step (1) is completely immersed in the catalyst solution obtained in step (2), and placed in a high-pressure reactor for hydrothermal reaction at 80-120° C. After the reaction is completed, the reaction product is washed with deionized water and anhydrous ethanol at least twice in sequence, and dried to obtain CoSeO3 / NF.

[0013] Preferably, the Co source in step (2) includes one or a combination of two or more of Co(NO3)2·6H2O, CoCl2·6H2O, Co(CH3COO)2·4H2O, and CoSO4·7H2O.

[0014] Preferably, the Se source in step (2) comprises one or a combination of two or more of SeO, SeO2, and SeO3.

[0015] Preferably, in step (2), the molar ratio between the Co source and the Se source is 4-7:1, and the mass concentration of the Co source in deionized water is 39-48 g / L.

[0016] Preferably, the pH in step (2) is 3.

[0017] Preferably, the ammonium salt in step (2) comprises one or a combination of two or more of NH4F, NH4Cl, NH4NO3, NH4HCO3.

[0018] Preferably, the hydrothermal reaction time in step (3) is 5-15 h.

[0019] Preferably, the hydrothermal reaction time in step (3) is 10 h.

[0020] Preferably, step (1) is carried out in the following manner:

[0021] The porous nickel foam is sequentially immersed in hydrochloric acid, anhydrous ethanol and deionized water for ultrasonic cleaning for at least 30 minutes, and then vacuum dried to obtain a nickel foam carrier.

[0022] Preferably, the concentration of hydrochloric acid in step (1) is 3 mol / L.

[0023] The present invention has the following beneficial effects:

[0024] (1) The present invention uses an electrolytic method to generate a sulfur oxidation reaction at the anode to selectively convert the sulfide solution into polysulfide or high-valent polysulfide, and then adds 0.5M H2SO4 to the electrolyte to directionally convert the polysulfide into sulfur, thereby cleverly realizing the sulfur recycling recovery in the sulfur-containing wastewater at the anode. The whole process does not generate any waste gas emissions, which can be called an "environmentally friendly" desulfurization technology. At the same time, hydrogen is synchronously and efficiently generated at the cathode. The whole process is simple and clear, with high operational flexibility. Parameters such as voltage and current can be adjusted at any time to accurately control the reaction process, and it is easy to realize automated operation;

[0025] (2) The present invention synthesizes a sea urchin structure composed of radial micron sheets in situ on a three-dimensional porous nickel foam (NF) substrate by a simple one-step hydrothermal method, wherein the surface of the micron sheets is assembled with staggered nanosheet arrays. The surface of this lamellar structure is a nano-conductive network that is interconnected. This unique design not only enhances the overall structural stability of the material, but also greatly increases the number of active sites, providing a rich material transfer path, thereby effectively improving the mass transfer efficiency. In addition, this structure can efficiently induce negative charge accumulation, so that the CoSeO3 / NF electrode material exhibits excellent sulfur oxidation reaction and hydrogen evolution reaction performance, which is suitable for sulfur recovery and efficient hydrogen regeneration processes. At the same time, the preparation conditions for preparing CoSeO3 / NF are mild, low-cost, and the raw materials are easily available, which has good prospects for industrial production;

[0026] (3) SeO3 in CoSeO3 2- There will be a synergistic effect between SeO3 and the transition metal element Co. 2- It can effectively adjust the electronic state of the Co site, thereby reducing the energy barrier of the hydrogen evolution reaction and optimizing the free energy of hydrogen adsorption, making the proton (H + ) are easier to be captured, thus promoting excellent electrocatalytic activity. In addition, the three-dimensional structure constructed by nanosheets can not only shorten the diffusion path of ions, but also reduce the self-aggregation of low-dimensional nanomaterials. These characteristics together ensure the stability and high efficiency of the catalyst in long-term use;

[0027] (4) The present invention has found through research that in the process of preparing CoSeO3 / NF by hydrothermal method, the hydrothermal time has a significant effect on the catalytic activity and selectivity of the catalyst. The research results show that, for the preparation process of the present invention, the performance of CoSeO3 / NF-1 synthesized by low-temperature hydrothermal reaction of CoSeO3 / NF for 10 h is better than that of CoSeO3 / NF-2 and CoSeO3 / NF-3 electrode materials synthesized by hydrothermal reaction for 5 h and 15 h. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 : SEM image of CoSeO3 / NF-1.

[0029] Figure 2 : XRD pattern of CoSeO3 / NF-1.

[0030] Figure 3 : Linear sweep voltammetry curves of CoSeO3 / NF-1, CoSeO3 / NF-2, CoSeO3 / NF-3, CoSeO3 / NF-4, and CoSe2 / NF-1.

[0031] Figure 4: LSV test comparison of CoSeO3 / NF-1 in HER||SOR and HER||OER coupling systems respectively.

[0032] Figure 5 : Chronoamperometry curves of CoSeO3 / NF-1 in HER||SOR and HER||OER coupling systems respectively. DETAILED DESCRIPTION

[0033] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.

[0034] The nickel foam in the following embodiments of the present invention is porous nickel foam purchased from Xingzhenghong Technology Co., Ltd. with a product number of XZH202201N.

[0035] Example 1

[0036] A CoSeO3 / NF electrode material for SOR and HER reactions, and a preparation method thereof is as follows:

[0037] (1) cutting the porous nickel foam into samples with a thickness of 0.1 cm, a length of 1.5 cm, and a width of 1 cm, and then immersing them in 3 mol / L hydrochloric acid, anhydrous ethanol, and deionized water for ultrasonic cleaning for 30 min, and then vacuum drying to obtain a nickel foam carrier;

[0038] (2) adding 2.00 g of CoCl2·6H2O and 0.16 g of SeO2 to 50 mL of deionized water, stirring and dispersing the mixture uniformly to obtain a dispersion, and adding NH4HCO3 to the dispersion to adjust the pH of the solution to 3 to obtain a catalyst solution;

[0039] (3) The nickel foam carrier obtained in step (1) is completely immersed in the catalyst solution obtained in step (2), and placed in a high-pressure reactor, and subjected to a hydrothermal reaction at 90° C. for 10 h. After the reaction is completed, it is naturally cooled to room temperature. The reaction product is washed twice with deionized water and anhydrous ethanol in sequence, and finally dried at 60° C. to obtain CoSeO3 / NF-1.

[0040] The CoSeO3 / NF-1 electrode material prepared in this example was characterized by scanning electron microscopy. Figure 1As shown in the figure, after hydrothermal synthesis, the catalyst CoSeO3 / NF-1 presents a unique sea urchin-like structure, which is composed of radially arranged micron-sized sheets. The surface of these micron-sized sheets is decorated with interlaced nanosheet arrays, showing a fine sense of hierarchy. This nano-network structure can significantly increase the exposure of active sites, thereby effectively promoting the electrocatalytic process. In addition, it can be seen that the thickness of the micron-sized sheet is 4μm.

[0041] As the instruction manual Figure 2 As shown, the XRD pattern of the catalyst CoSeO3 / NF-1 shows that CoSeO3 particles are successfully loaded on the surface of nickel foam.

[0042] Example 2 is the same as Example 1, except that the hydrothermal time in Example 2 is 5 hours. The obtained catalyst is recorded as CoSeO3 / NF-2.

[0043] Example 3 is the same as Example 1, except that the hydrothermal time in Example 3 is 15 h. The obtained catalyst is denoted as CoSeO3 / NF-3.

[0044] Comparative Example 1

[0045] The preparation method of CoSe2 / NF catalyst is as follows:

[0046] (1) cutting the porous nickel foam into samples with a thickness of 0.1 cm, a length of 1.5 cm, and a width of 1 cm, and then immersing them in 3 mol / L hydrochloric acid, anhydrous ethanol, and deionized water for ultrasonic cleaning for 30 min, and then vacuum drying to obtain a nickel foam carrier;

[0047] (2) Synthesis of Co(OH)2 / NF precursor: 50 mL of deionized water was measured with a measuring cylinder and placed in a polytetrafluoroethylene reactor. 2.00 g of CoCl2·6H2O, 0.46 g of NH4F and 1.21 g of urea were accurately weighed with an analytical balance and placed in the reactor. A clean magnetic rod was added and stirred thoroughly to form a uniform solution. The foamed nickel carrier was clamped with tweezers and placed in the reactor horizontally and immersed in the solution. The carrier was then subjected to hydrothermal reaction at 120°C for 6 h. After the reaction was completed, the carrier was naturally cooled to room temperature. The catalyst sample was taken out and rinsed with deionized water and anhydrous ethanol twice in sequence to remove the residue on the sample surface. The carrier was finally dried at 60°C to obtain Co(OH)2 / NF.

[0048] (3) Synthesis of Co(OH)2 / NF precursor: Place 0.4 g of selenium powder upstream of a quartz boat, and place the Co(OH)2 / NF obtained in step (2) downstream of the quartz boat. Place the quartz boat in a tube furnace, calcine in air at 450°C for 1 h, and cool naturally to room temperature to obtain CoSe2 / NF.

[0049] Comparative Example 2 is the same as Example 1, except that the pH in step (2) of Comparative Example 2 is 5. The obtained catalyst is recorded as CoSeO3 / NF-4.

[0050] Comparative Example 3 is the same as Example 1, except that the hydrothermal temperature in step (3) of Comparative Example 3 is 80°C.

[0051] Comparative Example 4 is the same as Example 1, except that the hydrothermal temperature in step (3) of Comparative Example 4 is 120°C.

[0052] Performance Testing

[0053] The performance of the catalyst was evaluated by linear sweep voltammetry. The hydrogen evolution reaction (HER) activity was tested in a 1.0 M NaOH aqueous solution using a three-electrode system. The SOR activity was tested in a mixed solution containing NaOH and Na2S (a mixed solution formed by dissolving 1 mol NaOH and 1 mol Na2S solid in 1 L of deionized water). The test results are shown in the attached manual. Figure 3 (Figure a corresponds to the linear sweep voltammetry curve of HER, and Figure b corresponds to the linear sweep voltammetry curve of SOR) and as shown in Table 1.

[0054] HER reaction: The working electrodes were the catalysts obtained in Examples 1-3 and Comparative Examples 1-4, respectively. A platinum electrode was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The linear scanning voltammetric curve test of HER was performed in the voltage range of 1.0-1.6 V (relative to Ag / AgCl) at a scan rate of 5 mV / s.

[0055] SOR reaction: The working electrodes were the catalysts obtained in Examples 1-3 and Comparative Examples 1-4, respectively. A platinum electrode was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The linear scanning voltammetric curve test of SOR was performed in the voltage range of -0.2 to -1.0 V (relative to Ag / AgCl) at a scanning rate of 5 mV / s.

[0056] Table 1

[0057]

[0058] As shown in Table 1, the performance of CoSeO3 / NF in hydrogen evolution and sulfur oxidation reactions far exceeds that of CoSe2 / NF. The reason is that compared with CoSe2, the urchin-like morphology of CoSeO3 / NF assembled by nanosheet arrays can maximize the exposure of active sites, significantly enhance electronic conductivity, maximize hydrogen evolution adsorption energy, and improve charge transfer ability, showing excellent electrochemical activity. At the same time, the reaction time, reaction pH and temperature also have a great influence on the performance of the catalyst. The performance of CoSeO3 / NF-1 synthesized by low-temperature hydrothermal reaction of CoSeO3 / NF for 10h is better than that of CoSeO3 / NF-2 and CoSeO3 / NF-3 electrode materials synthesized by hydrothermal reaction for 5h and 15h. The performance of CoSeO3 / NF-1 synthesized by CoSeO3 / NF at pH = 3 is also better than that of CoSeO3 / NF-4 synthesized at pH = 5. Compared with the hydrothermal reaction temperatures of 80℃ and 120℃, the CoSeO3 / NF-1 synthesized at 90℃ shows better catalytic performance. In summary, the CoSeO3 / NF-1 electrode material synthesized in the present invention shows more significant advantages in the field of hydrogen regeneration and integrated sulfur recovery.

[0059] Application Example 1

[0060] (1) Construction of HER||SOR coupling system performance: CoSeO3 / NF-1 was used as the cathode electrode and anode electrode of the H-type electrolytic cell, respectively, to construct a two-electrode system for testing. The cathode electrolyte was a 1.0 M NaOH aqueous solution, and the anode electrolyte was a mixed solution of 1 mol NaOH and 1 mol Na2S solid dissolved in 1 L deionized water. The diaphragm was a cationic membrane (DuPont, Nafion 117), which was Na + The transport of ions provides channels to maintain ionic charge balance and divide the anode / cathode regions. Linear sweep voltammetry tests were performed at a voltage of 0-2.5V, and the test results were compensated with 90% infrared.

[0061] (2) Performance of HER||OER coupling system: The test was conducted on a CHI660E electrochemical workstation, using the CoSeO3 / NF-1 electrode material obtained in Example 1 as the working electrode, the platinum electrode as the counter electrode, and the cathode and anode electrolytes were both 1.00 M NaOH aqueous solution. The HER||OER coupling system was tested at 5 mV·s in the range of 1.2-2.0 V (relative to Ag / AgCl). -1 The linear sweep voltammetry (LSV) curve was tested at a scan rate of , and 90% impedance compensation was adopted to obtain the final LSV curve.

[0062] Instructions attached Figure 4(a) is a comparison of the LSV tests of the HER||SOR and HER||OER coupling systems. The results show that at 100 mA cm -2 At a current density of , the HER||SOR coupling system only requires a voltage of 0.624 V to reach the corresponding current density, while the HER||OER system requires a voltage of 1.722 V, and the energy consumption is much higher than that of the HER||SOR system.

[0063] (3) Sulfur recovery from sulfur oxidation reaction and Faradaic efficiency of sulfur: 100 mA cm was applied to the HER||SOR two-electrode system -2 The current density was tested, and after the reaction was completed, 0.5M H2SO4 aqueous solution was added to the electrolyte in the anode chamber to make the pH of the electrolyte = 1, and sulfur was obtained. The Faraday efficiency (FE) of sulfur was calculated based on the recovered mass of sulfur. S ), the Faraday efficiency of HER||SOR is as shown in the instruction manual. Figure 4 (b) As shown in Figure 2, the Faraday efficiency (FE S ) is greater than 95%, and the sulfur production rate is about 1.29mmol min -1 gcatalyst -1 It can be seen that the CoSeO3 / NF-1 of the present invention can be used to successfully produce sulfur from sulfur-containing wastewater.

[0064] Application Example 2

[0065] Catalytic activity stability test: Tested by chronoamperometry (IT), the results are as attached to the instructions Figure 5 As shown, working currents of -0.1A and 0.1A were applied to two identical CoSeO3 / NF-1, respectively, and the electrolyte was replaced every 24 hours to test the catalytic activity stability of the catalyst during HER and SOR reactions, respectively.

[0066] Figure 5 (a) is the catalytic activity stability of CoSeO3 / NF-1 during the HER reaction. Figure 5 (b) is the catalytic activity stability of CoSeO3 / NF-1 during the SOR reaction. The results show that after each continuous operation for 24 hours, the current density of CoSeO3 / NF-1 shows a downward trend, but the current density is restored after the electrolyte is replaced. After 240 hours of durability testing, the current density generated by CoSeO3 / NF-1 during the HER and SOR reactions did not show obvious attenuation, proving that CoSeO3 / NF-1 has excellent electrocatalytic durability.

[0067] In summary, the CoSeO3 / NF-1 bifunctional catalyst obtained in the present invention shows significant advantages in hydrogen regeneration and integrated sulfur recovery, which not only helps to more accurately regulate the balance between sulfur supply and demand, but also provides new possibilities for promoting sustainable development.

[0068] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A CoSeO3 / NF electrode material for SOR and HER reactions, characterized in that: The preparation method comprises the following steps: (1) removing oxides and impurities on the surface of porous nickel foam to obtain a nickel foam carrier; (2) adding a Co source and a Se source into deionized water, stirring and dispersing them uniformly to obtain a dispersion, adding an ammonium salt into the dispersion to adjust the pH of the solution to 1-3, and obtaining a catalyst solution; (3) The nickel foam carrier obtained in step (1) is completely immersed in the catalyst solution obtained in step (2), and placed in a high-pressure reactor for hydrothermal reaction at 80-120° C. After the reaction is completed, the reaction product is washed with deionized water and anhydrous ethanol at least twice in sequence, and dried to obtain CoSeO3 / NF.

2. The CoSeO3 / NF electrode material for SOR and HER reactions according to claim 1, characterized in that: The Co source in step (2) includes one or a combination of two or more of Co(NO3)2·6H2O, CoCl2·6H2O, Co(CH3COO)2·4H2O, and CoSO4·7H2O.

3. The CoSeO3 / NF electrode material for SOR and HER reactions according to claim 1, characterized in that: The Se source in step (2) includes one or a combination of two or more of SeO, SeO2, and SeO3.

4. The CoSeO3 / NF electrode material for SOR and HER reactions according to claim 1, characterized in that: In step (2), the molar ratio of the Co source to the Se source is 4-7:1, and the mass concentration of the Co source in deionized water is 39-48 g / L.

5. The CoSeO3 / NF electrode material for SOR and HER reactions according to claim 1, characterized in that: The pH in step (2) is 3.

6. The CoSeO3 / NF electrode material for SOR and HER reactions according to claim 1, characterized in that: The ammonium salt in step (2) includes one or a combination of two or more of NH4F, NH4Cl, NH4NO3, and NH4HCO3.

7. The CoSeO3 / NF electrode material for SOR and HER reactions according to claim 1, characterized in that: The hydrothermal reaction time in step (3) is 5-15h.

8. The CoSeO3 / NF electrode material for SOR and HER reactions according to claim 7, characterized in that: The hydrothermal reaction time in step (3) is 10 h.

9. The CoSeO3 / NF electrode material for SOR and HER reactions according to claim 1, characterized in that: Step (1) is specifically performed according to the following method: The porous nickel foam is sequentially immersed in hydrochloric acid, anhydrous ethanol and deionized water for ultrasonic cleaning for at least 30 minutes, and then vacuum dried to obtain a nickel foam carrier.

10. The CoSeO3 / NF electrode material for SOR and HER reactions according to claim 1, characterized in that: The concentration of hydrochloric acid in step (1) is 3 mol / L.

Citation Information

Patent Citations

  • Water-containing leaf-shaped lamellar structure nano material, preparation method thereof and lithium ion energy storage application

    CN111769276A

  • Phosphorus-doped cobalt molybdate HER / SOR bifunctional catalyst, preparation method and application

    CN117845256A